Developing a framework to facilitate an improvement culture: the case of Saudi Arabia - Almaiman, Sulaiman; McLaughlin, Patrick; Al-Ashaab, Ahmed (Cranfield University, 2017)
This research explores aspects of organizational culture to facilitate continuous improvement within nonprofit organizations. Research shows that organizational culture plays a significant role in driving organizations and that they benefit from continuous improvement. The nonprofit sector contributes much to the economy and well-being, but is still often neglected; hence, Saudi nonprofit organizations are here the location for building a framework that promotes a culture of continuous improvement. In this qualitative research, grounded theory is the chosen approach. Eighteen interviews in nine organizations yielded data which, when analysed revealed forty emergent factors, classifiable into six initial themes developed by focus group participants. However, synthesising the framework is still in progress.
Keywords: Organizational culture; Continuous improvement; Nonprofit organizations